Caring for the caregivers: A cross-sectional study of the burden experienced by family caregivers of children with cancer in South Gujarat - Priyanka C Chovatiya; Mamta Rani Varma; Kavita G Bodar (Asian Journal of Medical Sciences, 2024)
Background: In India, family members undertake the care of a considerable number of patients with chronic illnesses like cancer at home, yet despite the recognition of their pivotal role as caregivers, scant attention is given to the suffering they endure. Aims and Objectives: The aim of the study is to study the sociodemographic characteristics of caregivers and children/adolescents with cancer undergoing cancer treatment and assess the caregiver’s burden of children/adolescents suffering from cancer. Materials and Methods: A cross-sectional study involving caregivers of children having cancer who were availing services at Cancer Institute (Lions Cancer Detection Center), New Civil Hospital, Surat, to identify the burden among caregivers of children of 0–19 years of age group. A total of 237 participants were enrolled in the study from June 2019 to November 2019. Using a standardized, validated version of the Zarit Burden Interview was used for data collection. Data entry into Microsoft Excel and analysis was done by Epi Info. Univariate analysis was done to calculate mean and standard deviation while bivariate analysis by Chi-square test. Results: The study population consisted of 99 (41.8%) males and 138 (58.2%) female caregivers aged 18–58 years. One hundred and twenty-five (52.7%) caregivers reported no or minimal burden while 64 (27.0%) caregivers reported mild-to-moderate burden. Conclusion: In view of the substantial burden on family caregivers coupled with the lack of an adequate number of cancer hospitals, there is a public health imperative to recognize this important group. All levels of health staff in cancer hospitals in developing countries should be sensitized to the various burdens faced by family caregivers.